PENGARUH COOPERATIVE TIPE SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA IPS KELAS III SD - Khoirul, Khoirul; Marli, Suhardi; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the cooperative effect of snowball throwing type on learning outcomes in learning social science class III State Elementary School 66 Pontianak City. The form of research used was quasi experimental with Nonequivalent Control Group Design. The sample in this study was class III A (control class) and class III B (experimental class) consisting of 61 people. Data collection techniques used were measurement techniques with data collection tools used in the form of student learning outcomes tests in the form of multiple choice totaling 50 questions. Based on the results of data analysis, the average learning outcomes of the control class students was 73.93 while the average learning outcomes of the experimental class students were 77.10. The results of hypothesis testing (t-test) using t-test obtained tcount of 5.6796 and ttable (a = 5% and dk = 60) of 2.0435, indicating that tcount (5.6796)> ttable (2.0435) . Then Ha was accepted. This means that there is an influence of learning outcomes between students taught with the Snowball Throwing cooperative learning model and students without the Snowball Throwing cooperative learning model. From the calculation of Effect size (ES), obtained 0.32 (medium criteria) Â Keywords: Model Cooperative Learning type Group Investigation, Learning Outcomes, Citizenship EducationÂ